Findings from two Arctic search and rescue exercises north of Spitzbergen. (3rd July 2019) - Gudmestad, Ove Tobias; Solberg, Knut Espen
ABSTRACT: With the implementation of the Polar Code in January 2017, the focus on search and rescue operations in polar waters have been increased due to the five-day survival requirement. This requirement poses a strain on all lifesaving appliances and causes the need for improved personal protection equipment, improved survival crafts and personal survival kits and possibly group survival kits. The paper reports on findings from search and rescue exercises north of Spitzbergen. The first exercise was carried out during late April 2016, utilizing SOLAS approved lifesaving appliances (LSA) equipment and the second exercise was conducted with improved LSA equipment during the first week of May 2017. Focus is on the ability to survive and the effectiveness of the improved LSA equipment. Furthermore, a discussion is given with respect to possible mitigation measures to ensure quick rescue to avoid the evacuated persons be exposed to an unnecessary long stay in the survival crafts. Of particular reference is the cruise industry and the industry's efforts to provide customers with visits to even more remote cruise locations. The study indicates significant gaps between the functionality provided by the LSA equipment and the functionality required to comply with the International Maritime Organization Polar Code requirement of survival for the expected time to rescue, minimum 5 days.